Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

By forming a LiCoO2 cladding layer doped with LiCoO2, including the spinel phase of Co3O4 and G oxides, the problem of performance attenuation of the positive electrode material at high voltages is solved, and higher gram capacity and good cycling performance are achieved, and the service life is extended.

CN119786566APending Publication Date: 2025-04-08JIANGSU DANGSHENG MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411975370.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The performance of the cathode material of lithium-ion batteries at high voltages is attenuated, resulting in a decrease in the capacity and circulation performance of grams, and a shortened service life.

Method used

LiCoO2 doped with M elements and Al elements is used as the body, and a LiCoO2 coating layer doped with G elements and Al elements is formed on its surface. The coating layer contains the oxides of Co3O4 and G of spinel phase to block the contact between the electrolyte and the material surface and stabilize the doped LiCoO2.

Benefits of technology

It improves the structural stability and electrochemical properties of the positive electrode active material at high voltage, extends the service life, and enhances the capacity and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a positive active material and a preparation method thereof, a positive pole piece, a battery and electric equipment, and relates to the technical field of batteries, the positive active material comprises a body and a coating layer formed on at least part of the surface of the body, the body comprises LiCoO2 doped with an element M and an element Al and first Co3O4, and the element M comprises at least one of Mg, Zr, Ni, Mn, La, Y and W; the coating layer comprises LiCoO2 doped with a G element and an Al element, second Co3O4 and an oxide of G, and the G element comprises at least one of Ti, Zr, Nb, La, Y, Ce, Mo and Sb. Therefore, the battery containing the positive electrode active material has excellent gram volume and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] The main components of lithium-ion batteries are electrolyte, diaphragm materials, positive electrode and negative electrode materials. Among them, the most widely used positive electrode active materials for lithium-ion batteries include lithium cobalt oxide materials (LiCoO 2 ), in order to meet the requirements of higher energy density of lithium-ion batteries, the active materials of lithium cobalt oxide cathodes are developed in the direction of high voltage (≥4.50V). However, the continuous increase in working voltage leads to more lithium ions being released from the lithium cobalt oxide structure during charging, and more Co 3+ Transformed into Co with higher valence and stronger oxidizability 4+ , which will bring more side reactions between the electrolyte and the material surface, resulting in the degradation of battery performance. In addition, due to the high voltage LiCoO 2 The increase in the amount of Co released in the cathode material causes oxygen to be released from the crystal structure, LiCoO 2 The oxygen released in the battery reacts with the electrolyte to produce a large amount of gas, which will deteriorate the storage performance of the battery and further deteriorate the overall performance of the battery. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device, wherein the battery containing the positive electrode active material has excellent gram capacity and cycle performance.

[0004] In one aspect of the present invention, the present invention provides a positive electrode active material, the positive electrode active material comprises a body and a coating layer formed on at least a portion of the surface of the body, the body comprises LiCoO doped with M element and Al element 2 , and Co 3 O 4 The M element includes at least one of Mg, Zr, Ni, Mn, La, Y, and W; the coating layer includes LiCoO doped with G and Al elements. 2 , and Co 3 O 4 and an oxide of G, wherein the G element includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

[0005] According to the positive electrode active material of the embodiment of the present invention, a coating layer is provided on the main body of the positive electrode active material, and the main body includes M element and Al element doped LiCoO 2, the coating layer includes G element and Al element doped LiCoO 2 , and a certain amount of spinel Co in the coating layer 3 O 4 and G oxides, which can block the doped LiCoO in the bulk and cladding layers 2 In contact with the electrolyte, and Co 3 O 4 The presence of G oxides can further stabilize the doped LiCoO in the bulk and coating layers. 2 , reducing lattice oxygen release, so that the prepared positive electrode active material has excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high voltage lithium cobalt oxide positive electrode active material.

[0006] In addition, the positive electrode active material according to the above embodiment of the present invention may also have the following additional technical features:

[0007] In some embodiments of the present invention, based on the total mass of the positive electrode active material, the first Co 3 O 4 The mass proportion m1 of the Co element is 100ppm-2000ppm, preferably 500ppm-800ppm.

[0008] In some embodiments of the present invention, based on the total mass of the positive electrode active material, the second Co 3 O 4 The mass proportion m2 of the Co element is 4000ppm-11000ppm, preferably 3000ppm-8000ppm.

[0009] In some embodiments of the present invention, the value of m2 / m1 is greater than or equal to 2, preferably 2-25, and more preferably 2-7.

[0010] In some embodiments of the present invention, based on the total mass of the positive electrode active material, the mass proportion m3 of the G element in the G oxide is 500 ppm-3000 ppm.

[0011] In some embodiments of the present invention, the second Co 3 O 4 The mass ratio m2 / m3 of the Co element in the oxide of G to the G element in the oxide of G is 1-10, preferably 3-6.

[0012] In some embodiments of the present invention, the G element includes Ti, La, Y, and Zr at the same time, and the G element also includes at least one of Ce, Mo, Nb, and Sb.

[0013] In some embodiments of the present invention, the chemical formula of the positive electrode active material includes:

[0014] (1-x)LiCo 1-a-b Al a M b O 2 ·xLiCo 1-c-d Al c G d O 2 Among them, LiCo 1-a-b Al a M b O 2 For the main body, LiCo 1-c- d Al c N d O 2 It is a coating layer, 0<x<0.06, a=0.020-0.040, b=0.004-0.025, c=0.040-0.200, d=0.050-0.200, M includes at least one of Mg, Zr, Ni, Mn, La, Y, and W, and G includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

[0015] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material, comprising:

[0016] The cobalt precursor doped with M element and Al element and the lithium source are mixed and sintered for the first time to obtain a body;

[0017] The main body, the Al-containing cobalt source and the G source are mixed and sintered for a second time to obtain a positive electrode active material.

[0018] Thus, the above-mentioned positive electrode active material can be prepared by this method, and the main body includes M element and Al element doped LiCoO 2 , the coating layer includes G element and Al element doped LiCoO 2 , and a certain amount of spinel Co in the coating layer 3 O 4 and G oxides, which can block the doped LiCoO in the bulk and cladding layers 2 In contact with the electrolyte, and Co 3 O 4 The presence of G oxides can further stabilize the doped LiCoO in the bulk and coating layers. 2, reducing lattice oxygen release, so that the prepared positive electrode active material has excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high voltage lithium cobalt oxide positive electrode active material.

[0019] In some embodiments of the present invention, the temperature of the first sintering is greater than the temperature of the second sintering.

[0020] In some embodiments of the present invention, the temperature of the first sintering is 1020°C-1100°C.

[0021] In some embodiments of the present invention, the first sintering time is 8h-20h.

[0022] In some embodiments of the present invention, the second sintering includes: pre-sintering at 850° C.-950° C. for 3 h-5 h, cooling to 750° C.-850° C., and sintering for 5 h-8 h.

[0023] In some embodiments of the present invention, the average particle size of the Al-containing cobalt source is 0.1 μm-2.0 μm.

[0024] In some embodiments of the present invention, the cobalt precursor doped with M element and Al element includes at least one of cobalt tetroxide doped with M element and Al element, cobalt carbonate doped with M element and Al element, and cobalt hydroxide doped with M element and Al element.

[0025] In some embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium acetate.

[0026] In some embodiments of the present invention, the Al-containing cobalt source includes at least one of Al-containing cobalt hydroxide, Al-containing cobalt tetraoxide, and Al-containing cobalt hydroxyl.

[0027] In some embodiments of the present invention, the G source includes at least one of G oxide and G fluoride.

[0028] In a third aspect of the present invention, the present invention provides a positive electrode plate, comprising the positive electrode active material described in the first aspect of the present invention.

[0029] In the fourth aspect of the present invention, the present invention provides a battery, comprising the positive electrode sheet described in the third aspect of the present application, so that the battery has excellent gram capacity and cycle performance.

[0030] In a fifth aspect of the present invention, the present invention provides an electrical device, comprising the battery described in the fourth aspect of the present invention.

[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail below, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The following is exemplary by reference to the embodiments, which are intended to be used to explain the present invention and cannot be understood as limiting the present invention.

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] In one aspect of the present invention, the present invention provides a positive electrode active material, the positive electrode active material comprises a body and a coating layer formed on at least a portion of the surface of the body, the body comprises LiCoO doped with M element and Al element 2 , and Co 3 O 4 The M element includes at least one of Mg, Zr, Ni, Mn, La, Y, and W; the coating layer includes LiCoO doped with G and Al elements. 2 , and Co 3 O 4 and an oxide of G, wherein the G element includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

[0035] The inventors found that by providing a coating layer on the main body of the positive electrode active material, the main body includes M element and Al element doped LiCoO 2 , the coating layer includes G element and Al element doped LiCoO 2 , while having spinel phase Co in the coating layer 3 O 4 and G oxides, spinel phase Co 3 O 4 The oxides of G can block the doped LiCoO in the bulk and cladding layers. 2 In contact with the electrolyte, and Co 3 O 4 The presence of the oxide of G, the two work together to reduce the Co in the positive electrode active material under high voltage conditions. 4+ concentration, reducing Co 4+The side reaction with the electrolyte can further stabilize the doped LiCoO in the bulk and coating layer. 2 , reducing lattice oxygen release, so that the prepared positive electrode active material has excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high voltage lithium cobalt oxide positive electrode active material.

[0036] The present invention constructs a LiCoO2 doped with active materials (G and Al elements) on the surface of the main body on the basis of stabilizing the main body structure. 2 ) and metal oxide coating layers, so that the positive electrode active material has a higher gram capacity and good cycle life at a voltage of 4.50V and above.

[0037] According to an embodiment of the present invention, based on the total mass of the positive electrode active material, the first Co 3 O 4 The mass proportion of Co element in m1 is 100ppm-2000ppm, for example, it can be 100ppm, 500ppm, 1000ppm, 1500ppm, 2000ppm, etc. 3 O 4 The mass proportion of the Co element in the electrolyte is controlled within the above range, which can not only isolate the doped lithium cobalt oxide from the electrolyte to a certain extent, but also prevent the excessive content from reducing the gram capacity of the positive electrode active material, thereby improving the stability of the positive electrode active material and improving the gram capacity and cycle performance. According to other embodiments of the present invention, m1 is 500ppm-800ppm.

[0038] It can be understood that in the examples of the present application, 1ppm=1μg / g.

[0039] According to an embodiment of the present invention, based on the total mass of the positive electrode active material, the second Co 3 O 4 The mass proportion of Co element in m2 is 4000ppm-11000ppm. For example, it can be 4000ppm, 5000ppm, 7000ppm, 9000ppm, 10000ppm, 11000ppm, etc. 3 O 4 The mass percentage of Co in the coating layer is controlled within the above range. 3 O 4The content of m2 is higher than that of the main body, and the effect of isolating the main body and the cobalt oxide doped in the coating layer from contacting with the electrolyte is more obvious. Moreover, within the range of m2, the content of m2 is not too much to reduce the gram capacity of the positive electrode active material, and the stability of the positive electrode active material can be further improved, thereby improving the gram capacity and cycle performance. According to other embodiments of the present invention, m2 is 3000ppm-8000ppm.

[0040] It can be understood that in the embodiments of the present application, the coating layer refers to the portion from the surface of the positive electrode active material layer to the inner core, and the thickness thereof accounts for 1 / 10 of the average particle size of the positive electrode active material.

[0041] According to an embodiment of the present invention, the value of m2 / m1 is greater than or equal to 2, for example, it can be 2, 5, 10, 15, 20, 25, 30, etc., and the mass ratio of the two is controlled within the above range. The Co of the spinel phase in the coating layer 3 O 4 The content of m1 / m2 is higher than that of the main body, and the effect of isolating the main body and the cobalt oxide doped in the coating layer from contacting with the electrolyte is more obvious. Moreover, within the above range of m1 / m2, the content is not too much to reduce the gram capacity of the positive electrode active material and the transmission of lithium ions, which can further improve the stability of the positive electrode active material, thereby improving the gram capacity and cycle performance. According to other embodiments of the present invention, the value of m2 / m1 is 2-25, for example, 2-7.

[0042] According to an embodiment of the present invention, based on the total mass of the coating layer and the total mass of the positive electrode active material, the mass proportion m3 of the G element in the G oxide is 500ppm-3000ppm. For example, it can be 500ppm, 1000ppm, 2000ppm, 3000ppm, etc. By controlling the mass proportion of the G element in the G oxide in the positive electrode active material within the above range, the contact between the lithium cobalt oxide doped in the body and the coating layer and the electrolyte can be further reduced, the cycle performance of the positive electrode active material can be improved, and the oxygen release of the positive electrode active material can be reduced, and the excessive G oxide can be reduced to affect the performance of the capacity of the positive electrode active material, thereby improving the gram capacity and cycle performance of the positive electrode active material.

[0043] According to an embodiment of the present invention, the second Co 3 O 4 The mass ratio m2 / m3 of the Co element in the G element in the oxide of G is 1-10, for example, it can be 1, 3, 5, 7, 9, 10, etc. The mass ratio of the metal elements of the two oxides in the coating layer is controlled within the above range, which can better play the role of reducing the high voltage condition Co 4+ concentration, reducing Co 4+ The side reaction with the electrolyte can further stabilize the doped LiCoO in the bulk and coating layer.2 , reducing lattice oxygen release, so that the prepared positive electrode active material has excellent structural stability and electrochemical performance, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high voltage lithium cobalt oxide positive electrode active material. According to other embodiments of the present invention, the value of m2 / m3 is 3-6.

[0044] It can be understood that in the embodiment of the present invention, Co 3 O 4 The content of oxides of G can be determined by the following method:

[0045] (1) adding the positive electrode active material to a sulfuric acid-phosphoric acid mixture, and adding a metal ion sulfate solution, and stirring thoroughly to dissolve;

[0046] (2) filtering the solution obtained in step (1) to obtain a filtrate and a filter cake, and washing the filter cake with pure water multiple times;

[0047] (3) adding the filter cake in step (2) to a strong acid solution, heating, dissolving, and evaporating, repeating for 3 times to fully dissolve the filter cake; after cooling, constant volume is obtained to obtain a solution;

[0048] (4) ICP test element content in solution.

[0049] Step (1) can dissolve the LiCoO containing doping elements in the bulk and coating layer. 2 and the elements in its structure, the filter cake obtained in step (2) mainly contains elements in the form of oxides, and the oxides can be dissolved and fixed in volume through steps (3) and (4) to obtain the content of the elements in the form of oxides.

[0050] According to an embodiment of the present invention, the G element includes Ti, La, Y, and Zr at the same time, and the G element also includes at least one of Ce, Mo, Nb, and Sb. The Ti, La, Y, Zr, and Al elements, and at least one of Ce, Mo, Nb, and Sb work together to further extend the actual service life of the high-voltage lithium cobalt oxide positive electrode active material.

[0051] According to an embodiment of the present invention, the chemical formula of the positive electrode active material includes:

[0052] (1-x)LiCo 1-a-b Al a M b O 2 ·xLiCo 1-c-d Al c G d O 2 ;

[0053] Among them, LiCo1-a-b Al a M b O 2 For the main body, LiCo 1-c-d Al c N d O 2 It is a coating layer, 0<x<0.06, a=0.020-0.040, b=0.004-0.025, c=0.040-0.200, d=0.050-0.200, M includes at least one of Mg, Zr, Ni, Mn, La, Y, and W, and G includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

[0054] As an example, x can be 0.01, 0.02, 0.03, 0.04, 0.05, etc., a can be 0.020, 0.030, 0.040, etc., b can be 0.004, 0.005, 0.01, 0.015, 0.020, 0.025, etc., c can be 0.040, 0.100, 0.150, 0.200, etc., and d can be 0.050, 0.100, 0.150, 0.200, etc.

[0055] It can be understood that in the above chemical formula, x represents the amount of substance in the coating layer of the positive electrode active material. The chemical formula of the positive electrode active material is limited to the above chemical formula. On the basis of stabilizing the structure of the main body, a LiCoO layer containing active materials (G element and Al element doped) is constructed on the surface of the main body. 2 ) and metal oxide coating layers, so that the positive electrode active material has a higher gram capacity and good cycle life at a voltage of 4.50V and above.

[0056] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material. According to an embodiment of the present invention, the method comprises:

[0057] S100: mixing a cobalt precursor doped with M element and Al element and a lithium source, and sintering for the first time to obtain a main body.

[0058] According to an embodiment of the present invention, the temperature of the first sintering is 1020°C-1100°C. For example, it can be 1020°C, 1050°C, 1100°C, etc. By controlling the temperature of the first sintering within the above range, LiCoO doped with M element and Al element can be generated. 2 , and a certain amount of spinel phase Co 3 O 4, which makes the prepared positive electrode active material have excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high-voltage lithium cobalt oxide positive electrode active materials.

[0059] According to an embodiment of the present invention, the first sintering time is 8h-20h, for example, 8h, 10h, 15h, 20h, etc., and the temperature of the first sintering is controlled within the above range to generate LiCoO doped with M element and Al element. 2 , and a certain amount of spinel phase Co 3 O 4 , which makes the prepared positive electrode active material have excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, extending the actual service life of high-voltage lithium cobalt oxide positive electrode active materials.

[0060] According to an embodiment of the present invention, the cobalt precursor doped with M element and Al element includes at least one of cobalt tetroxide doped with M element and Al element, cobalt carbonate doped with M element and Al element, and cobalt hydroxide doped with M element and Al element.

[0061] According to an embodiment of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium acetate.

[0062] S200: mixing the main body, the Al-containing cobalt source and the G source, and sintering for a second time to obtain a positive electrode active material.

[0063] According to an embodiment of the present invention, the second sintering includes: pre-sintering at 850℃-950℃ for 3h-5h, cooling to 750℃-850℃, and sintering for 5h-8h. For example, the pre-sintering temperature can be 850℃, 900℃, 950℃, etc., the pre-sintering time can be 3h, 4h, 5h, etc., the sintering temperature after cooling can be 750℃, 800℃, 850℃, etc., and the sintering time after cooling can be 5h, 6h, 7h, 8h, etc. Using the above second sintering method, the step sintering process of high-temperature sintering first and low-temperature sintering can generate LiCoO doped with G element and Al element on the surface of the body. 2 , and a certain amount of spinel phase Co 3 O 4 The oxides of and G make the prepared positive electrode active material have excellent structural stability and electrochemical properties, especially high gram capacity and good cycle performance under high voltage, which prolongs the actual service life of high voltage lithium cobalt oxide positive electrode active material.

[0064] According to an embodiment of the present invention, the average particle size of the Al-containing cobalt source is 0.1 μm-2.0 μm, for example, it can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2.0 μm, etc. Controlling the average particle size of the Al-containing cobalt source within the above range is conducive to generating a positive electrode active material with better performance, so that a certain amount of spinel phase Co in the coating layer 3 O 4 The oxides of G and G are beneficial for the battery containing them to have higher gram capacity and good cycle performance at high voltage, extending the actual service life of high-voltage lithium cobalt oxide positive electrode active materials.

[0065] According to an embodiment of the present invention, the Al-containing cobalt source includes at least one of Al-containing cobalt hydroxide, Al-containing cobalt tetraoxide, and Al-containing cobalt hydroxyl.

[0066] According to an embodiment of the present invention, the G source includes at least one of G oxide and G fluoride.

[0067] According to an embodiment of the present invention, the first sintering and the second sintering are performed in an air atmosphere.

[0068] In summary, the positive electrode active material obtained by the above method can obtain a positive electrode active material with a main body and a coating layer material. On the basis of stabilizing the main body structure, a LiCoO 2 ) and metal oxide coating layers, so that the positive electrode active material has a higher gram capacity and good cycle life at a voltage of 4.50V and above.

[0069] The method for preparing the positive electrode active material provided by the present invention has a simple process flow, easily controllable reaction conditions, and is suitable for industrial production.

[0070] In a third aspect of the present invention, the present invention provides a positive electrode sheet. According to an embodiment of the present invention, the positive electrode sheet comprises the positive electrode active material described in the first aspect of the present invention, or the positive electrode active material prepared by the method described in the second aspect.

[0071] According to an embodiment of the present invention, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material, wherein the positive electrode collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode collector can be aluminum foil.

[0072] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0073] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0074] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0075] It should be noted that the features and advantages described above for the positive electrode active material and the preparation method thereof are also applicable to the positive electrode plate and will not be described in detail here.

[0076] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises at least one of the positive electrode sheets described in the third aspect.

[0077] As an example, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0078] According to an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be a copper foil.

[0079] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and the like.

[0080] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0081] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0082] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0083] According to some other embodiments of the present invention, there is no particular restriction on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restriction.

[0084] According to some other embodiments of the present invention, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte can be in a gel state or a fully solid state. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution, and the electrolyte solution includes a lithium salt and a solvent.

[0085] According to some specific embodiments of the present invention, the lithium salt may include at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate or lithium bis(trifluoromethylsulfonyl)imide.

[0086] According to some specific embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0087] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0088] It should be noted that the above-mentioned features and advantages described for the positive electrode plate are also applicable to the solid-state battery and will not be repeated here.

[0089] In a fifth aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device includes the above-mentioned battery. According to an embodiment of the present invention, the electric device may include but is not limited to a mobile phone, a laptop computer, an electric vehicle, etc.

[0090] It should be noted that the features and advantages described above for the battery are also applicable to the electrical device and will not be repeated here.

[0091] Below, the embodiment of the present invention is described. The embodiment described below is exemplary, is only used to explain the present invention, and cannot be interpreted as limiting the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0092] Example 1

[0093] (1) Weigh Mg, Al, and Y-doped Co at a molar ratio of Li:Co = 1.045. 3 O 4 and Li 2 CO 3 , use a high-speed mixer to mix evenly, sinter at 1060℃ in air atmosphere for 12h, crush and sieve to obtain lithium cobalt oxide process product (bulk) LiCo 0.9666 Mg 0.005 Al 0.0264 Y 0.0020 O 2 ;

[0094] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 and ZrO 2After weighing according to the mass ratio of 1:0.0390:0.0010:0.0013:0.0006:0.0007, the mixture was evenly mixed, sintered at 900°C for 4h and then at 800°C for 6h in an air atmosphere, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S1 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0095] Comparative Example 1

[0096] Lithium cobalt oxide is prepared according to the method of Example 1, except that in step (2), the lithium cobalt oxide process product, Al-containing cobalt hydroxide, TiO 2 , Y 2 O 3 ,La 2 O 3 and ZrO 2 The mass ratio was replaced with 1:0.0390:0:0:0:0 for mixing and sintering (the sintering conditions were the same as in Example 1) to obtain a lithium cobalt oxide positive electrode material D1 with a coating layer. The element content thereof was tested by ICP and shown in Table 2.

[0097] Comparative Example 2

[0098] Lithium cobalt oxide is prepared according to the method of Example 1, except that in step (2), the lithium cobalt oxide process product, Al-containing cobalt hydroxide, TiO 2 , Y 2 O 3 ,La 2 O 3 and ZrO 2 The mass ratio was replaced with 1:0:0.0010:0.0013:0.0006:0.0007 for mixing and sintering (the sintering conditions were the same as in Example 1) to obtain a lithium cobalt oxide positive electrode material D2 with a coating layer. The element content thereof was tested by ICP and is shown in Table 2.

[0099] Example 2

[0100] (1) Weigh Mg, Al, Ni, and Mn-doped Co(OH) at a molar ratio of Li:Co = 1.05 2 and LiOH, mixed evenly using a high-speed mixer, sintered at 1040°C in an air atmosphere for 15 hours, and then crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.963 Mg 0.004 Al 0.03 Ni 0.002 Mn 0.001 O 2 ;

[0101] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2, Y 2 O 3 ,La 2 O 3 and CeO 2 After weighing according to the mass ratio of 1:0.0446:0.0010:0.0013:0.0006:0.0005, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S2 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0102] Example 3

[0103] (1) Weigh Mg, Al, and Zr-doped Co at a molar ratio of Li:Co = 1.045. 3 O 4 and Li 2 CO 3 , mixed evenly using a high-speed mixer, sintered at 1050°C in an air atmosphere for 12 hours, crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.9658 Mg 0.00 5 Al 0.028 Zr 0.0012 O 2 ;

[0104] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt tetraoxide, and the Y 2 O 3 , Nb 2 O 5 and MoO 3 After weighing according to the mass ratio of 1:0.0321:0.0019:0.0004:0.0015, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S3 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0105] Example 4

[0106] (1) Weigh Mg and Al-doped CoCO according to the molar ratio of Li:Co = 1.040 3 and Li 2 CO 3 , mixed evenly using a high-speed mixer, sintered at 1080°C in an air atmosphere for 10 hours, crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.961 Mg 0.006 Al 0.033 O 2 ;

[0107] (2) The lithium cobalt oxide process product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 、ZrO 2 and Sb 2 O 3 After weighing according to the mass ratio of 1:0.0266:0.0010:0.0013:0.0012:0.0007:0.0006, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S4 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0108] Example 5

[0109] (1) Weigh Mg and Al-doped CoCO according to the molar ratio of Li:Co = 1.040 3 and Li 2 CO 3 , mixed evenly using a high-speed mixer, sintered at 1080°C in an air atmosphere for 10 hours, crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.961 Mg 0.006 Al 0.033 O 2 ;

[0110] (2) The lithium cobalt oxide process product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 、ZrO 2 and Sb 2 O 3 After weighing according to the mass ratio of 1:0.0306:0.0010:0.0013:0.0012:0.0007:0.0006, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S5 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0111] Example 6

[0112] (1) Weigh Mg and Al-doped CoCO according to the molar ratio of Li:Co = 1.040 3 and Li 2 CO 3 , mixed evenly using a high-speed mixer, sintered at 1080°C in an air atmosphere for 10 hours, crushed and sieved to obtain the lithium cobalt oxide process product LiCo0.961 Mg 0.006 Al 0.033 O 2 ;

[0113] (2) The lithium cobalt oxide process product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 、ZrO 2 and Sb 2 O 3 After weighing according to the mass ratio of 1:0.0356:0.0010:0.0013:0.0012:0.0007:0.0006, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S6 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0114] Example 7

[0115] (1) Weigh Mg and Al-doped CoCO according to the molar ratio of Li:Co = 1.040 3 and Li 2 CO 3 , mixed evenly using a high-speed mixer, sintered at 1080°C in an air atmosphere for 10 hours, crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.961 Mg 0.006 Al 0.033 O 2 ;

[0116] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 、ZrO 2 and Sb 2 O 3 After weighing according to the mass ratio of 1:0.0411:0.0010:0.0013:0.0012:0.0007:0.0006, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S7 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0117] Example 8

[0118] (1) Weigh Mg, Al, and La-doped Co at a molar ratio of Li:Co = 1.05 3O 4 and LiO, mixed evenly using a high-speed mixer, sintered at 1075°C in an air atmosphere for 8 hours, and then crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.9673 Mg 0.004 Al 0.028 La 0.0007 O 2 ;

[0119] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt hydroxide, and the TiO 2 , Y 2 O 3 ,La 2 O 3 、CeO 2 and MoO 3 After weighing according to the mass ratio of 1:0.0483:0.0010:0.0013:0.0006:0.0006:0.0008, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S8 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0120] Example 9

[0121] (1) According to the molar ratio of Li:Co = 1.05, weigh Mg, Al, Y, and Zr doped Co 3 O 4 and LiOH, mixed evenly using a high-speed mixer, sintered at 1045°C in an air atmosphere for 16 hours, and then crushed and sieved to obtain the lithium cobalt oxide process product LiCo 0.9616 Mg 0.005 Al 0.031 Y 0.018 Zr 0.0006 O 2 ;

[0122] (2) the lithium cobalt oxide product prepared in step 1, the Al-containing cobalt tetraoxide, and the Y 2 O 3 ,La 2 O 3 、ZrO 2 and Nb 2 O 5 After weighing according to the mass ratio of 1:0.0371:0.0013:0.0006:0.0007:0.0002, the mixture was evenly mixed, sintered at 900°C for 4h in an air atmosphere, cooled to 800°C for 6h, cooled naturally, crushed and sieved to obtain lithium cobalt oxide material S9 with a core-shell structure. The element content was tested by ICP and shown in Table 2.

[0123] The following method was used to determine the mass percentage of the Co element in the bodies obtained in step (1) of the above-mentioned embodiments and comparative examples:

[0124] (1) adding the positive electrode active material to a sulfuric acid-phosphoric acid mixture, and adding a metal ion sulfate solution, and stirring thoroughly to dissolve;

[0125] (2) filtering the solution obtained in step (1) to obtain a filtrate and a filter cake, and washing the filter cake with pure water multiple times;

[0126] (3) adding the filter cake in step (2) to a strong acid solution, heating, dissolving, and evaporating, repeating for 3 times to fully dissolve the filter cake; after cooling, constant volume is obtained to obtain a solution;

[0127] (4) ICP test element content in solution.

[0128] The first Co obtained above 3 O 4 The mass proportion of the Co element in the positive electrode is based on the mass proportion of the bulk. The mass proportion of the Co element obtained is divided by the total amount of raw materials added in the preparation method to obtain the mass proportion of the positive electrode active material, the first Co 3 O 4 The mass percentage of Co element in .

[0129] The mass proportion of each element in the finally prepared positive electrode active material is measured again according to the above method, and the mass proportion of each element in the form of oxide (including Co 3 O 4 Co element in the form of Co, based on the mass of the positive electrode active material, will be 3 O 4 The mass percentage of Co elements in the form of positive electrode active materials, the first Co 3 O 4 The mass proportion of the Co element in the positive electrode active material can be obtained based on the total mass of the positive electrode active material. 3 O 4 The mass of Co element in the MgO accounts for m2.

[0130] The specific calculation process is shown in Table 1 and Table 2.

[0131] Table 1

[0132]

[0133]

[0134] The parameters for preparing the positive electrode active materials in the above embodiments and comparative examples are specifically shown in Table 2.

[0135]

[0136] 1) Prepare button cells according to the following steps:

[0137] 9.2 g of the positive electrode active material prepared above, 0.4 g of acetylene black and 0.4 g of polyvinylidene fluoride (PVDF) were mixed, coated on an aluminum foil and dried, and stamped with a pressure of 100 MPa to obtain a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm. The positive electrode sheet was then placed in a vacuum drying oven and dried at 120°C for 12 h.

[0138] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm; the separator uses a polyethylene porous membrane with a thickness of 25 μm; the electrolyte uses 1 mol / L LiPF 6 The electrolyte is a mixture of equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC).

[0139] The positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into a 2025 button cell in an Ar gas glove box with a water content and an oxygen content less than 5 ppm.

[0140] 2) 0.1C discharge capacity, 1C cycle 50 cycles performance test

[0141] 0.1C discharge gram capacity test:

[0142] The button cell was placed for 24 hours. After the open circuit voltage was stable, it was charged to a cut-off voltage of 4.6 V at a current density of 20 mA / g to the positive electrode. It was charged at a constant voltage of 4.6 V for 30 minutes and then discharged to a cut-off voltage of 3.0 V at the same current density. The 0.1C discharge gram capacity was tested. The results are shown in Table 3.

[0143] Cycle performance test:

[0144] The button cell was activated by constant current and constant voltage charge and discharge cycles in the range of 3.0-4.6 V. The charge and discharge regime was as follows: After charging and discharging at a rate of 0.1C for 2 weeks, the cell was considered an activated cell.

[0145] Using an activated battery, the cycle retention rate of the material was examined at a current density of 0.5C in the voltage range of 3.0-4.6V and a temperature of 45°C for 50 cycles. The first charge capacity and the first discharge capacity of the battery were recorded. First efficiency = first discharge gram capacity / first charge gram capacity × 100%, cycle retention rate = (50th discharge gram capacity / first discharge gram capacity) × 100%. The results are shown in Table 3.

[0146] Table 3

[0147]

[0148] It can be seen from Table 3 that the lithium-ion battery prepared using the positive electrode active material prepared in the embodiment of the present invention has high discharge capacity, first efficiency and capacity retention rate.

[0149] From Table 1, Table 2 and Table 3, compared with the embodiment, the coating layer of Comparative Example 1 contains lithium cobalt oxide and the second Co 3 O 4 , but the lithium cobalt oxide in the coating layer is not doped with the G element and the coating layer does not contain G oxide, the stability of the coating layer is deteriorated, and the side reaction with the electrolyte is relatively violent. Although the discharge capacity and the first effect are acceptable, the cycle performance of the battery is significantly reduced; the coating layer of comparative example 2 does not contain lithium cobalt oxide and the second Co 3 O 4 The positive electrode active material contains excess lithium. During the charge and discharge process, the excess lithium is released during the charge process and cannot be embedded in the body during the discharge process, resulting in a significant decrease in discharge capacity and initial efficiency. At the same time, because the coating layer does not contain lithium cobalt oxide and the second Co 3 O 4 , the cycle performance is also significantly reduced.

[0150] In the positive electrode active materials of Examples 4 to 6, the second Co 3 O 4 The content gradually increases, the cycle retention rate increases, but the capacity gradually decreases; compared with Examples 5 and 6, the positive electrode active material of Example 7 has a 3 O 4 The content is too high, resulting in a decrease in both capacity and cycle performance; the coating layer of the positive electrode active material of Examples 1, 2, 3, 8, and 9 does not meet the following conditions: the G element includes Ti, La, Y, and Zr at the same time, and the G element also includes at least one of Ce, Mo, Nb, and Sb, so that the cycle performance of the battery in Examples 1, 2, 3, 8, and 9 is significantly reduced compared with Examples 4-6.

[0151] The positive electrode active material of the embodiment of the present application is used, and the battery containing the positive electrode active material has excellent gram capacity and cycle performance.

[0152] In summary, it can be seen from the above results that the lithium-ion battery prepared using the core-shell structure positive electrode active material prepared in the embodiment of the present invention has a high discharge gram capacity and capacity retention rate.

[0153] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0154] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a body and a coating layer formed on at least a portion of the surface of the body; The body includes LiCoO2 doped with M element and Al element, and a first Co3O4, wherein the M element includes at least one of Mg, Zr, Ni, Mn, La, Y, and W; The coating layer includes LiCoO2 doped with G element and Al element, and a second Co3O4 and G oxide, wherein the G element includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

2. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass proportion m1 of the Co element in the first Co3O4 is 100ppm-2000ppm, preferably 500ppm-800ppm; Optionally, based on the total mass of the positive electrode active material, the mass proportion m2 of the Co element in the second Co3O4 is 4000ppm-11000ppm, preferably 3000ppm-8000ppm; Optionally, the value of m2 / m1 is greater than or equal to 2, preferably 2-25, and more preferably 2-7.

3. The positive electrode active material according to claim 1 or 2, characterized in that: Based on the total mass of the positive electrode active material, the mass proportion m3 of the G element in the G oxide is 500ppm-3000ppm; Optionally, the mass ratio m2 / m3 of the Co element in the second Co3O4 to the G element in the G oxide is 1-10, preferably 3-6; Preferably, the G element includes Ti, La, Y, and Zr at the same time, and the G element also includes at least one of Ce, Mo, Nb, and Sb.

4. The positive electrode active material according to claim 1 or 2, characterized in that: The chemical formula of the positive electrode active material includes: (1-x)LiCo 1-a-b Heavy a M b O2·xLiCo 1-c-d Heavy c G d O2: Among them, LiCo 1-a-b Al a M b O2 is the main body, LiCo 1-c-d Al c G d O2 is a coating layer, 0<x<0.06, a=0.020-0.040, b=0.004-0.025, c=0.040-0.200, d=0.050-0.200, M includes at least one of Mg, Zr, Ni, Mn, La, Y, and W, and G includes at least one of Ti, Zr, Nb, La, Y, Ce, Mo, and Sb.

5. A method for preparing the positive electrode active material according to any one of claims 1 to 4, characterized in that: include: The cobalt precursor doped with M element and Al element and the lithium source are mixed and sintered for the first time to obtain a body; The main body, the Al-containing cobalt source and the G source are mixed and sintered for a second time to obtain a positive electrode active material.

6. The method according to claim 5, characterized in that The temperature of the first sintering is greater than the temperature of the second sintering.

7. The method according to claim 5 or 6, characterized in that: The temperature of the first sintering is 1020°C-1100°C; Optionally, the first sintering time is 8h-20h.

8. The method according to claim 5 or 6, characterized in that: The second sintering includes: pre-sintering at 850° C.-950° C. for 3 h-5 h, cooling to 750° C.-850° C., and sintering for 5 h-8 h.

9. The method according to claim 5 or 6, characterized in that: The average particle size of the Al-containing cobalt source is 0.1 μm-2.0 μm; Optionally, the cobalt precursor doped with M element and Al element includes at least one of cobalt tetroxide doped with M element and Al element, cobalt carbonate doped with M element and Al element, and cobalt hydroxide doped with M element and Al element; Optionally, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, and lithium acetate; Optionally, the Al-containing cobalt source includes at least one of Al-containing cobalt hydroxide, Al-containing cobalt tetraoxide, and Al-containing cobalt hydroxyl; Optionally, the G source includes at least one of G oxide and G fluoride.

10. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 4.

11. A battery, characterized in that: Including the positive electrode sheet as described in claim 10.

12. An electrical equipment, characterized in that: Comprising the battery of claim 11.